Increasing the frequency of testicular self-examination behavior in college men - Tani, Crystal R., author; Hamilton, Scott B., advisor (Colorado State University. Libraries, 2002)
The effects of five hierarchically-ordered treatment interventions were evaluated in terms of their ability to increase testicular self-examination (TSE) in 164 college men over a 6-month period. The five interventions included: (1) No Treatment ControL (2) Informational Brochure (Treatment Condition A), (3) Video Taped Testimonial with TSE demonstration (Treatment Condition B), (4) Live Demonstration, Guided Practice, and Feedback (Treatment Condition C), and (5) Participant Discussion (Treatment Condition D). TSE behavior, behavioral intention (i.e., stages of change measure), testicular cancer (TC) knowledge and attitudes measure, and general health behaviors were examined at pre-treatment, 1 month, 2 1/2 month, and 6 month follow-up periods.

In general, results indicated that the most complex interventions (i.e., B, C, and D) were most effective in increasing TSE behavior and behavioral intentions. Participants in the most complex treatment conditions (i.e., B, C, and D) were more likely than the No Treatment Control and condition A to conduct self-examinations and progress toward maintenance of TSE at the 1 and 2 1/2 month follow-up. Although no differences in TC attitudes were found, knowledge of TC and TSE increased at the 1 month follow-up, for all conditions except the No Treatment Control. Regardless of condition, participants who practiced TSE regularly, compared to inconsistent self-examiners were more likely to feel confident they could correctly perform a self-examination, believed that TSE is helpful in detecting testicular cancer, and perceived their family and friends to be supportive of TSE. Regular self-examiners compared to inconsistent self-examiners also reported more physical and psychological health maintenance practices. Minimal differences were found between treatment conditions at the 6 month follow-up which appears to be due to a large participant attrition rate. Limitations and implications of the study are discussed along with the need for developing strategies to enhance maintenance.
Keywords: psychotherapy; oncology; public health; behavioral sciences; physical examinations; men; college students; behavioral psychology; clinical psychology